2022
DOI: 10.1111/apps.12398
|View full text |Cite
|
Sign up to set email alerts
|

You raise me up and I reciprocate: Linking empowering leadership to organizational citizenship behavior and unethical pro‐organizational behavior

Abstract: Although empowering leadership is generally thought to be beneficial to employees and organizations, an emerging stream of work shows its potential negative impact. Drawing upon social exchange theory, we propose an integrated model that simultaneously examines the benefits and costs of empowering leadership. Specifically, we propose that team‐level empowering leadership can relate to both organizational citizenship behavior (OCB) and unethical pro‐organizational behavior (UPB). We also examine the mediating r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 96 publications
0
19
0
Order By: Relevance
“…When subordinates are empowered by having great control at work, they can encourage them to feel a deeper meaning for what has been done in their work. Empowering leadership becomes an organizational stimulus to influence its members or team [ 24 ]. Thus, they can foster a high sense of self-confidence and competence to be loyal to the organization.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…When subordinates are empowered by having great control at work, they can encourage them to feel a deeper meaning for what has been done in their work. Empowering leadership becomes an organizational stimulus to influence its members or team [ 24 ]. Thus, they can foster a high sense of self-confidence and competence to be loyal to the organization.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The research on unethical pro-organization in the workplace focuses on its antecedents (Mo et al, 2023;Liu et al, 2022). Researchers hope to reduce UPB in enterprises and to reduce the potential long-term costs associated with UPB by studying the factors influencing or forming mechanisms of UPB (Griep et al, 2023;Liao et al, 2023;Wang et al, 2023).According to the literature review, the antecedents of UPB mainly focus on personal factors, leadership factors and organizational factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a growing body of research on leadership factors, the influence relationship between UPB and servant leadership, empowering leadership, transformational-transactional leadership, ethical leadership, charismatic leadership have all been studied. For example, Honglei Wang discussed team-level empowering leadership that produces organizational citizenship behaviour (OCB) when perceived obligation is high, while producing UPB when perceived obligation is low, which proves the existence of empowering leadership's dark side (Wang et al, 2023). A large number of studies on organizational factors emerged, such as Abusive supervision (Yan et al, 2023), high-performance work systems (Jabari et al, 2023), highcommitment human resource management (Song & Christian, 2023), power distance orientation (Li et al, 2023), performance-approach goal orientation (Mo et al, 2022) and so on.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To motivate employees to exhibit more OCBs, the relationship of leadership with follower OCB has received substantial attention from scholars because leadership plays a key role in affecting follower behaviors. Considerable research has demonstrated that employee OCB can be driven by various leadership behaviors such as humble leadership, transformational leadership, and empowering leadership (Cho et al, 2021; Wang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%